2014
DOI: 10.1177/1090820x14548212
|View full text |Cite
|
Sign up to set email alerts
|

Filling Effects, Persistence, and Safety of Dermal Fillers Formulated With Stem Cells in an Animal Model

Abstract: Stem cells have the potential to improve the aesthetic effects and longevity of dermal fillers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 45 publications
(45 reference statements)
1
18
0
Order By: Relevance
“…Furthermore, patients have also noted associated improvements in psychosocial function. 29 Emerging studies have shown the benefit of combination therapy of filler with other technologies such as ablative fractional laser, 30 stem cells, 31 and platelet-rich plasma therapy. 32 Indeed, with the development of new dermal fillers on the horizon, in conjunction with other minimally invasive procedures such as neuromodulators, injectables, lasers, and devices, our ability to optimally recontour the aging face will continue to advance.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, patients have also noted associated improvements in psychosocial function. 29 Emerging studies have shown the benefit of combination therapy of filler with other technologies such as ablative fractional laser, 30 stem cells, 31 and platelet-rich plasma therapy. 32 Indeed, with the development of new dermal fillers on the horizon, in conjunction with other minimally invasive procedures such as neuromodulators, injectables, lasers, and devices, our ability to optimally recontour the aging face will continue to advance.…”
Section: Resultsmentioning
confidence: 99%
“…Injected cellular material loaded onto or injected with the matrix has been shown to secrete biomaterials to recruit local soft tissue cells to prolong tissue bulk without the risk of foreign body reaction. 41 Much as the cellular material loaded onto a scaffold could change characteristics of the scaffold, it is also possible that the scaffold can have changes on the cells.…”
Section: Biologic Materialsmentioning
confidence: 99%
“…A total of 70% of stem cells remain in the injection site after 3 months. These suggested stem cells have the potential to improve the esthetic effects and longevity of dermal fillers [31].…”
Section: Hyaluronic Acid (Ha)mentioning
confidence: 99%